Abuse liability assessment of the JUUL system in two nicotine concentrations compared to combustible cigarette, nicotine gum and comparator electronic nicotine delivery system. (1st December 2020) - Goldenson, Nicholas I.; Buchhalter, August R.; Augustson, Erik M.; Rubinstein, Mark L.; Van Hoof, Dennis; Henningfield, Jack E.
Highlights: Abuse liability of the JUUL System (JS) in 5.0 % and 3.0 % nicotine was assessed. Comparators included combustible cigarette, 4 mg nicotine gum and VUSE Alto (5.0 %). Abuse liability of both JS is lower than cigarettes and higher than nicotine gum. Abuse liability of JS 5.0 % is somewhat higher than JS 3.0 %. Abuse liability of JS 5.0 % and 3.0 % is somewhat lower than VUSE Alto 5.0 %. Abstract: Background: To assess the abuse liability of the JUUL System (JS) in 5.0 % (59 mg/mL) and 3.0 % (35 mg/mL) nicotine concentrations. Methods: Adult smokers (N = 146; 45.9 % female; mean age = 41.29 years) were randomized to one of four study flavor arms and then to a within-subjects cross-over sequence for five test product categories: (1) JS 5.0 % nicotine concentration; (2) JS 3.0 % nicotine; (3) usual brand (UB) cigarette; (4) 4 mg mint nicotine gum; (5) comparator ENDS (VUSE Alto 5.0 % nicotine). Products were tested by ad libitum use (5 min for ENDS and cigarette; 30 min for gum); nicotine pharmacokinetic (PK) parameters and subjective effects were assessed following use. Results: Maximum plasma nicotine concentration (Cmax-BL ), rate of plasma nicotine rise and total nicotine exposure (AUC0–60-BL ) of UB cigarette were significantly greater than all other test products. The comparator ENDS was significantly greater than 5.0 % and 3.0 % JS and nicotine gum on Cmax-BL, rate of plasma nicotine rise, and AUC0–60-BL ; Cmax-BL of JS 5.0 % was significantly greater than JS 3.0 % and nicotine gum. Product liking and satisfying effects were significantly highest for the UB cigarette; JS products and comparator ENDS did not significantly differ and were rated higher than nicotine gum on most subjective measures. Conclusions: These results suggest that the abuse liability of both 5.0 % and 3.0 % JS is: (1) substantially lower than UB cigarette; (2) somewhat lower than comparator ENDS; and (3) higher than nicotine gum. Additionally, the abuse liability of JS 5.0 % is somewhat higher than JS 3.0 %.